PENDAMPINGAN KEWIRAUSAHAAN MELALUI PENERAPAN PENYUSUNAN LAPORAN KEUANGAN PADA UMKM BERBASIS SAK EMKM - Supriadi, Iman (Manajerial : Jurnal Manajemen dan Sistem Informasi, 2020)
Financial statements are related to financial information in a company which can be utilized to break down the organization's circumstance and evaluate the organization's ability in a different period. In the bookkeeping cycle for a period can be found out as indicated by the requirements of day by day, week after week, month to month, quarterly, four months, a half year, or once every year. This examination plans to make it simpler for SMEs to get ready money related reports that are observing the norms that have been in power on January 1, 2018. This exploration is performed at Surabaya SME Aklirik, who has not made money related reports following SAK EMKM. This exploration utilizes a subjective enlightening technique, which is an investigation portraying an issue. Information assortment is done by perception, meeting, and documentation. This exploration was completed to perceive the issues that occurred at the MSME and to make money related reports adhering to the relevant IFRS EMKM benchmarks. The consequences of this examination show that MSMEs have issues in making money related reports, to be specific the absence of thought with respect to overseeing budget reports and the absence of HR, which are not adequate in making budgetary reports. Fiscal reports dependent on EMKM SAK, to be specific the announcement of money related position, salary proclamation, and notes to the budget summaries.Laporan keuangan merupakan sebuah informasi yang berkaitan keuangan di perusahaan dimana dapat dipakai untuk menganalisa keadaan perusahaan serta menilai kapasitas perusahaan dalam periode tersendiri. Pada siklus akuntansi untuk satu periode bisa dipastikan sesuai keperluan harian, mingguan, bulanan, triwulanan, empat bulan, enam bulan, atau satu tahun sekali. Riset ini mempunyai tujuan untuk mempermudah pelaku UMKM dalam membuat laporan keuangan yang sesuai dengan dengan standard yang sudah berlaku pada 1 Januari 2018. Riset ini dipertunjukkan pada UMKM Surabaya Aklirik yang belum membuat laporan keuangan sesuai SAK EMKM. Riset ini memakai cara deskriptif kualitatif, yang merupakan studi pendeskripsian suatu masalah. Pengambilan data dilaksanakan dengan pengamatan, wawancara, serta dokumentasi. Riset ini dikerjakan untuk mengenali masalah yang berlangsung pada UMKM itu serta untuk membuat laporan keuangan sesuai dengan dengan standard EMKM IFRS yang berlaku. Hasil riset ini memperlihatkan jika UMKM itu mempunyai permasalahan dalam men create laporan keuangan, yakni kurangnya pertimbangan mengenai mengatur laporan keuangan serta kurangnya jumlah Sumber Daya Manusia dimana tidak mencukupi dalam membuat laporan keuangan. Laporan keuangan berdasar EMKM SAK, yakni laporan posisi keuangan, laporan laba rugi, serta catatan atas laporan keuangan.